Bacteria Associated with Septicemia in Children and their Antimicrobial Sensitivity Pattern, Kano, Nigeria - E, Kashibu; G.U, Ihesiulor; S. I, Adeleke; M.H, Tasabeeh (Asian Journal of Biological and Life Sciences, 2012)
The study is associated with childhood septicemia and their antimicrobial susceptibility pattern. A total of 2446 samples of blood culture of patients age less than 12 years were cultured from patients admitted into paediatric ward of Aminu Kano between January 2007 to December 2008. Bacteria isolates and their antibiogram were determined. Out of the 2446 patients investigated, 224 (9.2%) yielded significant bacterial growth while 2222 (90.8%) shared no evidence of bacterial growth. One hundred and eleven 111(49.6%) were males and 113(50.4%) were females giving a male to female ratio of 1:1 and the mean age 15 years. The peak of bacteria isolation was high in age group < 1 year 116(51.8%), followed by 8-10 years 28(12.5%) and group 12years 27(12%). Gram negative bacteria were sensitive to gentamycin, ofloxacin, amoxicillin, and resistant to Augmentin, ampicillin, cloxacillin, chloramphenicol. In conclusion, the study has identified the common bacterial pathogens associated with childhood septicemia and their antimicrobial sensitivity pattern.However,more periodic studies for clearer understanding of local epidemiology of childhood septicemia and designing of antibiotic policy to prevent antibiotic resistance should be carried out.